The physical-chemical analysis of ka zeolite obtained from local kaolin - Mukhammadjonov, Mirjalol; Rakhmatkarieva, Firuza; Oydinov, Mukhlis (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this study, AKF-78 grade Angren kaolin was used to synthesize KA zeolite. The obtained metakaolin and KCl were mixed in a 1:1 molar ratio. The prepared mixture was treated with a 2M NaOH solution and heated in an autoclave for 28 hours at 100°C. Based on the XRD data of the KA zeolite obtained through hydrothermal synthesis, it was compared with the peaks of LTA zeolite crystals. The KA zeolite synthesized from Angren kaolin through hydrothermal synthesis was found to fully correspond to the formula Al10H72K4.63Na6O91.32Si25.38 based on the XRD data. Furthermore, it was determined that the KA zeolite consists of the following elemental composition: O-51.2%, Si-25%, Al-10%, K-6.3%, Na-4.8%, and H-2.5%. The degree of crystallization and amorphicity of the zeolite was also determined. The degree of crystallization of KA zeolite was found to be 29.09%, while the degree of amorphicity was 70.91%. In the analysis of the catalytic or adsorption properties of the zeolites, crystal sizes are of significant importance. The LTA zeolite and the synthesized KA zeolite were compared using X-ray diffraction (XRD).